Searching And Amassin G The Essential Elements Of Knowledge: Toward The Transcendental One - Triyuwono, Iwan; Gafï¬kin, Michael J.R (The International Journal of Accounting and Business Society, 1994)
The aim of this study is to introduce a preliminary meth odological foundation of research that may be used as a basis for advancing accounting knowledge. It is designed especially to capture the meanings of social reality which construted by and as the result of interactions among members of Muslim society, economic systems, and accounting practices in Indonesia. The study attempts to combine and extend symbolic interactionism, a perspective of social psyphology, with Islamic values, that is, the concept of faith, knowledge and action. The modification, in terms of extending symbolic interactionism is indispensably conducted to adapt a social-religious environment in which the research will be carried out. Knowledge nearly completely externalized and desacralized, especially among those segments of human race which have become transformed by the process of modernization, and that bliss [qudrah, isikmah, and rahmah] which is the frail of union with the One with and an aspect of the perfume of the sacred has become well-nigh unattainable and beyond the grasp of the vast majority of those who walk upon the earth (Nasr1981,1).